Researcher Positionality: Ways to Include it in a Qualitative Research Design - Prashneel Ravisan Goundar (International Journal of Qualitative Methods)
When conducting research, a researcher’s perspective and worldview are referred to as positionality. It also “reflects the position that the researcher has chosen to adopt within a given research study” and describes the researcher’s relationship to their research subjects. What the researcher chooses to study, how it is carried out, and the outcomes are all influenced by their position. In this paper, I argue that the positionality of a researcher is shaped by a variety of factors, including gender, race, personal experiences, values, and beliefs. These factors then influence the researchers’ assumptions, methods of accessing and interacting with participants, the questions they pose, and how they interpret the findings. For higher degree research in the social sciences, there should be a section that clarifies researcher positionality. Making these declarations gives the study clarity and credibility in that the researcher is aware of their ‘insider and outsider hat’ so to say. This paper discusses ways in which Masters, Doctor of Education, Doctor of Social Work, Doctor of Teaching English to Speakers of Other Languages, and Ph.D. scholars can explain positionality in their research design. Crucial elements that must be disclosed in the study are the identities, viewpoints, and positions of the researchers. This work contributes to the growing corpus of scholarship on researcher positionality, which is based on my findings as a novice researcher conducting qualitative research. My paper takes an inductive systematic review approach which relates to noting observations and seeking to find patterns within them. I provide examples from my Ph.D. thesis which looked at academic English writing skills of first-year undergraduate students. The examples will be helpful to novice researchers and post-graduate students interested in providing precision in conducting qualitative methodology and examining positionality in their study. They can use the article as a starting point in approaching the concept of researcher positionality and ways in which it can be embedded in their study design.